Rhabdomyolysis and acute kidney injury from neurotoxic common krait envenomation: A case report (Indian Journal of Case Reports, 2026)
The common krait is a highly venomous snake endemic to South Asia. It is known primarily for its potent neurotoxicity. Although neurological manifestations such as descending paralysis are well described, rhabdomyolysis and acute kidney injury (AKI) are exceptionally rare. We report a case of rhabdomyolysis and AKI seen in a 36-year-old male with type 2 diabetes who presented 26 h after a confirmed bite by a common krait with dark-colored urine and leftlower-limb weakness. Laboratory investigations revealed marked rhabdomyolysis and myoglobinuria. Progressive renal dysfunction developed despite aggressive hydration, necessitating two sessions of hemodialysis. The patient also developed localized cellulitis requiring surgical fasciotomy. Renal recovery was achieved by day 8, and the patient was discharged with outpatient follow-up. This case broadens the clinical spectrum of common krait envenomation and underscores the need for continued observation after anti-snake venom administration.